Nursing Students’ Emotional State and Perceived Competence During the COVID-19 Pandemic: The Vital Role of Teacher and Peer Support - Utvær, Britt Karin; Torbergsen, Hanne; Paulsby, Tove Engan; Haugan, Gørill (Frontiers in Psychology, 2022)
Background: The COVID-19 pandemic led to a shutdown of society and created sudden and long-lasting changes in teaching practices, forcing many nursing students to study remotely at home. These students’ relatedness with their teachers and peers has been limited and mainly online. Several studies have indicated that students’ emotional state and mental health have been negatively affected by the pandemic, representing a serious challenge for many countries. Because they only use digital tools, online students have perceived a decline in teacher and peer support. Likewise, these students have reported feelings of sadness, loneliness, anxiety, and stress, affecting their learning and competence development. Aims: To investigate the associations between peer support, teacher support, emotional state, and perceived competence in nursing students during the pandemic. Methods: This cross-sectional study collected quantitative survey data from 329 nursing students at a large university in Norway. Structural equation modeling was used to test five associations between peer support, teacher support, emotional state, and perceived competence. Results: Teacher support had a significant direct effect on perceived competence, while peer support almost had a significant direct effect. However, emotional state was directly affected by peer support and had a direct impact on perceived competence. Hence, teacher and peer support are important to nursing students’ perceived competence. Conclusion: During the COVID-19 pandemic, both peer and teacher support can significantly support students’ competence development. Therefore, students should utilize the support of their teachers and peers in a structured manner to bolster their competence development.